Eddy Current Field Analysis for Permanent Magnetic Governor - Xu Wei; Sun Jianjun (Jixie chuandong)
As a new adjustable speed and energy conservation equipment,permanent magnetic governor is installed between motor and loads,using the magnetic circuit coupling principle,the speed control is realized through adjust air coupling area.Firstly,combined with the correlation theory of electromagnetic,the mathematical model of transient eddy current field is built.Then the static analysis of permanent magnetic governor is carried out,the static copper rotor flux distribution and magnetic induction intensity are obtained.Finally,through the finite element simulation of motion eddy current,the eddy current field formation mechanism and some factors affecting on eddy current field are analyzed,a theoretical basis for the bearing capacity of the permanent magnetic governor is provided.